Effects of polymorph transformation via mercerisation on microcrystalline cellulose fibres and isolation of nanocrystalline cellulose fibres - Osman Al-Edrus, Syeed Saifulazry; Chuah, Teong Guan; Md. Tahir, Paridah; Aung, Min Min; Zainudin, Edi Syams (Universiti Putra Malaysia Press, 2017)
Cellulose I can be irreversible transformed into cellulose II via mercerisation or regeneration treatments. In the past few decades, mercerisation was used mainly to improve fibre properties for textile industries. A few studies have focused on the effects of mercerisation treatment on the cellulose polymorph itself and after it was downscaled to nanosize. This study aims to characterise the micro size crystalline cellulose after complete polymorph conversion via mercerisation technique and investigate its effects on isolation to nanosize crystalline cellulose. A microcrystalline cellulose (MCC) was purchased and converted into cellulose II via mercerisation technique. Sulphuric acid hydrolysis was carried-out to produce nanocrystalline cellulose (NCC). The MCC and NCC of different polymorphs were then characterised and analysed for its crystallography, morphology, particles size distribution and thermal stability using wide-angle X-ray diffraction (WXRD), electron microscopes, dynamic light scattering analyser and thermogravimetric analyser, respectively. Both MCC and NCC fibres showed complete conversion of cellulose I to cellulose II and decrement of crystallinity index (CI). Electron micrographs revealed that both cellulose II polymorph fibres (MCC II and NCC II) were morphological affected. The analysis of size distribution and dimension measurement confirmed that mercerisation treatment causing increment in fibre diameter and shortened length. The thermal stability of both cellulose II polymorph fibres (MCC II and NCC II) was also found to be improved.